2021
DOI: 10.4014/jmb.2108.08038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enterotoxigenic Escherichia coli on Microbial Communities during Kimchi Fermentation

Abstract: The diverse microbial communities in kimchi are dependent on fermentation period and temperature. Here, we investigated the effect of enterotoxigenic Escherichia coli (ETEC) during the fermentation of kimchi at two temperatures using high-throughput sequencing. There were no differences in pH between the control group, samples not inoculated with ETEC, and the ETEC group, samples inoculated with ETEC MFDS 1009477. The pH of the two groups, which were fermented at 10 and 25 o C, decreased rapidly at the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition, the hybrids represented diverse serotypes (O2:H25 (2), O2:H27 (1), O8:H8 (1), O8:H9 (4), O100:H30 (7), O141:H29 (1), O148:H7 (1), O155:H21 (4), O168:H8 (5), and O174:H2 (1)] and sequence types [ST446 (7), ST1021 (5), ST21 (4), ST74 (4), ST785 (1), ST670 (2), ST1780 (1), ST1782 (1), ST10 (1), and ST726 (1)). Previous studies have revealed the diversity of sequence types and serotypes (>40) among STEC/ETEC hybrid strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the hybrids represented diverse serotypes (O2:H25 (2), O2:H27 (1), O8:H8 (1), O8:H9 (4), O100:H30 (7), O141:H29 (1), O148:H7 (1), O155:H21 (4), O168:H8 (5), and O174:H2 (1)] and sequence types [ST446 (7), ST1021 (5), ST21 (4), ST74 (4), ST785 (1), ST670 (2), ST1780 (1), ST1782 (1), ST10 (1), and ST726 (1)). Previous studies have revealed the diversity of sequence types and serotypes (>40) among STEC/ETEC hybrid strains.…”
Section: Discussionmentioning
confidence: 99%
“…The DEC pathotypes include enteropathogenic E. coli (EPEC), Shiga toxin-producing E. coli (STEC), enterotoxigenic E. coli (ETEC), enteroinvasive E. coli (EIEC), and enteroaggregative E. coli (EAEC). Many of these pathotypes are foodborne pathogens that raise public health concerns and cause several outbreaks in industrialized and developing countries [7][8][9]. STEC and ETEC are major causes of diarrhea in humans and animals worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature plays a crucial role in the growth, metabolism, and subsequent product synthesis of bacteria [61][62][63][64]. Some bacteria are sensitive to temperature changes, with alterations in temperature having a significant impact on their product synthesis [6,63,65]. Therefore, we investigated the growth and synthesis of 2-PE and IAA in Enterobacter sp.…”
Section: Effect Of the Temperature On The Growth And The Products Syn...mentioning
confidence: 99%
“…The intricate interactions between the fermentation process, lactic acid bacteria (LAB) strains, and the ingredients used to make kimchi (e.g., garlic, salt, ginger) are highly responsible for the health benefits that kimchi proudly possesses (Lee et al, 2011). During fermentation, LAB strains undergo metabolism to produce organic acids, H2O2, and bacteriocins that prevent the proliferation of pathogenic bacteria such as Enterotoxigenic Escherichia coli (ETEC) (Lee et al, 2021;Park et al, 2014). LAB strains have previously shown the ability to enrich the immune system, produce bioactive substances, and even lower cholesterol levels (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is recommended to use 2.5%-3.0% salt in kimchi for anticancer and antimutagenic effects (Park et al, 2014). Additionally, acidity levels, which help eliminate pathogenic bacteria, tend to increase more rapidly at higher fermentation temperatures (Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%